"What She Told Us Made the world of Difference": Carers' Perspectives on A Hospice at Home Service. Issue 3 (September 2013) - McKay, Elizabeth A.; Taylor, Ann E.; Armstrong, Claire
This paper explores the expectations and needs of current and bereaved carers whose relatives received care at home from a palliative care team. Aim: A hospice at home service was established in 2006 to provide patients with care in their own homes. We examined whether this model of care was helpful in mitigating carers' burden and in enabling terminally ill patients to be cared for and die at home. Methods: This study utilized a survey and interviews. Participants were carers in the midwest of Ireland. Survey responses from 122 carers were analyzed using SPSS 18.0 (SPSS Inc., 2009); interviews with 15 carers were also conducted. Results: Carers' expectations of the service were often exceeded, and quality of care dimensions were rated highly. Future improvements could include facilitating discussions on place of death and offering bereavement support. Conclusion: The service is supporting carers in facilitating their relatives' choice to die at home.